The specifics of adhesion function of endothelium in various clinical variants of primary mitral valve prolapse - A. V. Yagoda; N. N. Gladkikh; L. N. Gladkikh (Кардиоваскулярная терапия и профилактика)
Aim. To assess the condition of adhesion function of endothelium in various clinical variants of primary mitral valve prolapse (MVP). Material and methods. Totally, 91 patient studied with primary MVP at the age 21 (19-24) y. First grade mitral regurgitation was found in 45,1% and II — in 54,9% patients. MVP was solitary variant (6,6%) and comorbid with 1-3 minor anomalies of the heart (93,4%). Doppler-echocardiography was done on Vivid07 equipment (Israel). The grade of systemic involvement of connective tissue was 2 (1,5-4,0) points. Controls were 10 healthy persons, matched by age, sex, smoking, body mass index. By the immune enzyme method we checked plasmatic concentrations of L-, E-, Р-selectins, ICAM-1, VCAM-1, PECAM-1 (Bender MedSystems GmbH, Austria). Findings are presented as mediana (25-75 percentiles). Results. In MVP patients the levels of Е-selectin — 43,0 (33,7-54,8) ng/ mL, ICAM-1 — 669,9 (546,4-883,3) ng/mL and VCAM-1 — 925,0 (707,5- 1215,0) ng/mL, were significantly higher, and the level of РЕСАМ-1 — 49,8 (40,4-63,2) ng/mL, in opposite, lower than in control group. L- and P-selectins levels in MVP group were measured as relevant to controls values (p>0,05). In regurgitation cases of II degree, the level of E-selectin and ICAM-1 were maximal (p<0,05). Values of VCAM-1 in MVP patients independently from degree of regurgitation were significantly higher than controls values. There was moderate direst relation of the quantity of minor heart anomalies and level of ICAM-1 (rs=+0,30, р<0,05). In MVP group with increased E-selectin significantly higher was aorta diameter at the level of Valsalva sinuses — 2,5 (2,3-2,7) cm, than in PMV without increased E-selectin level — 2,3 (2,2-2,5) cm (р<0,05).Conclusion. In patients with primary MVP there is an increase of circulating concentrations of E-selectin, ICAM-1, VCAM-1, that represents the level of adhesion, and witnesses about subclinical endothelial dysfunction. For screening evaluation of severity of adhesion disorders of endothelium in MVP it is important to take into account its hemodynamic significance, multiple minor heart anomalies and data on aorta diameter on the level of Valsalva sinuses.